Adrenal Leiomyoma: a Rare Tumor Presented as an Incidentaloma in a Women with Ovarian Mature Cystic Teratoma - Bastakoti, Shankar; Lamichhane, Nirmal; Shrestha, Sadina; Dhungana, Ishan (Nepalese Journal of Cancer, 2019)
Adrenal leiomyoma is a rare neoplasm and usually associated with adrenal vein or its tributaries. These are benign in nature and are composed of smooth muscle cells. A sixty years Normotensive, non-HIV lady presented with right adnexal mass diagnosed as Mature Cystic Teratoma along with adrenal incidentalomas for which laparoscopic adrenalectomy was done and histopathology diagnosis was Leiomyoma. These are more common in immunocompromised patients especially HIV and or EBV infection. Adrenal incidentalomas can have a hormone secreting functions or they can be malignant tumors hence a proper evaluation and treatment should be performed.